Evaluation Of Usefulness To Investors Of Different Accounting Estimators Of Earnings - Simulation Approach - Discussion - Rappaport, Allen (Journal of Accounting Research, 1968)
Earnings informativeness, Simulation, Outside investors, Accounting estimators